A New Family to the ANOC groups : A study of stelae CG 20077 and CG 20098 - Rosell, Pablo Martín (2021)
The Middle Kingdom stelae found at Abydos are some of the most important sources of information to analyze and reconstruct Egyptian society. This article aims at providing a study and translation of two Middle Kingdom stelae that are preserved in the Grand Egyptian Museum in Giza and in the Egyptian Museum in Cairo. They are stela CG 20077, which belongs to an individual called Nemtu, and stela CG 20098, which belongs to a man called Nemtyemmer. The family relations attested in both stelae suggest that they could be part of the same family group and consequently constitute a new Abydos North Offering Chapel (ANOC). This paper also offers an analysis of the ANOC and proposes that these stelae should be added to the ANOC groups. Lastly, we attempt to identify the social identities represented in both stelae and the possible social and geographical origin of this family.
Keywords: Egypt; Middle Kingdom; Abydos; ANOC; Stelae; Society